Low protein diet score: a novel diet quality index and predictor of disease progression in patients with chronic kidney disease - Rouhani, Mohammad Hossein; Mortazavi Najafabadi, Mojgan; Azadbakht, Leila (Progress in Nutrition, 2018)
Background and Aim: Patients with chronic kidney disease (CKD) have been recommended to consume a low protein diet. However, there is no specific index for evaluating amounts of dietary protein and CKD progression in these patients. The objective of this study was to define a low protein diet score (LPDS) as a predictor of CKD progression and an index of diet quality in patients with CKD.  Methods: For this cross-sectional study, two hundred twenty seven eligible subjects with CKD (stage 3 and 4) were selected. We used a validated food frequency questionnaire to assess dietary intake of patients. LPDS was defined based on the 3 cut of points: >2 gr/kg (score=1), 1.01-2 gr/kg (score=2) and ≤ 1 gr/kg (score=3). Renal function (i.e., blood urea nitrogen and serum creatinine) and cardiometabolic variables (i.e., low density lipoprotein, triglyceride, total cholesterol, fasting blood sugar and high sensitivity C-reactive protein) were measured by biochemical assessment. As dietary intakes of sodium, potassium, phosphorus, saturated fatty acid and cholesterol are important, we used intake of these nutrients to assess diet quality. Results: Patients who received higher scores, had better diet quality because they consumed lower amounts of phosphorus, potassium, saturated fatty acid and cholesterol (P